Work Environment and Depressive Symptoms of Webtoon Writers - Jinwoo Lee; Jeehee Min; Yu Min Lee; Min Young Park; Hyoung-Ryoul Kim (Elsevier, 2024)
Background: Webtoon, a digital form of comics created in the Republic of Korea, has spread widely with advantages that anyone can become a cartoonist and that autonomy of creation is guaranteed. The purpose of this study is to identify the working conditions of webtoon writers and analyze the relationship between these conditions and depressive symptoms. Methods: A survey was carried out on webtoon writers and a survey data of 312 webtoon writers were analyzed. The questionnaire included basic socio-demographic characteristics, webtoon writers' contractual type, fields of activity (webtoon creator, story writer, illustrator), and working environment (labor discretion etc.). We investigated depressive symptoms and analyzed its relation to the work environment of webtoon writers. Results: Webtoon writers were exposed to long working hours, high labor intensity, limited labor discretion, negative comments from readers, and had a high prevalence of depressive symptoms. Compared to story writers who contracted directly with platforms, story writers and the illustrators who contracted with content providers (CPs) were 9.51 times (OR = 9.51, 95% CI = 1.47 - 61.33) and 6.47 times (OR = 6.47, 95% CI = 1.08 - 38.75) more likely to have depressive symptoms, respectively. Conclusions: This study emphasizes the urgent necessity to improve the overall working environment in the webtoon industry and implement measures to tackle the escalating mental health challenges faced by illustrators and story writers contracted with CPs, especially given the increasing popularity of novel comics.